Pengaruh Partisipasi Penyusunan Anggaran, Kejelasan Sasaran Anggaran, dan Profesionalisme Sumber Daya Manusia terhadap Kinerja Manajerial - Denny Cendra Bhakti; Endar Pituringsih; Erna Widiastuty (Universitas Islam Negeri Alauddin Makassar, 2015)
The aim of this study is to analyze empirical evidence the influence of budget participation, budget goal clarity and professionalism of human resources of the managerial performance of government of West Nusa Tenggara. Population in this study is Structural Echelons II, III and IV in Government agencies scope West Nusa Tenggara province, as much as 1,075 people. Samples in this study as many as 89 people from 23 governmen agencies and using Slovin method. Before the test the first hypothesis tested the validity and reliability of the instrument , the classical assumption test and multiple linear regression analysis. The result show that simultaneous participation variable budgeting, budget goal clarity and professionalism of human resources affect the managerial performance at government agencies Provincial Government of NTB. Only, budget goal clarity and professionalism of human resources a significant positive affect, while the budgeting participation negatively impact significantly.